Autothermal pyrolysis of peat in conditions of free movement in layer; MATEC Web of Conferences; Vol. 19 : The 2nd International Youth Forum "Smart Grids", Tomsk, Russia, October 6-10, 2014 - Kazakov A. V. Aleksandr Vladimirovich (2014, 2014)
Title screen